Current Status of Poultry Recombinant Virus Vector Vaccine Development - Haoran Wang; Jiaxin Tian; Jing Zhao; Ye Zhao; Huiming Yang; Guozhong Zhang (Vaccines, 2024)
Inactivated and live attenuated vaccines are the mainstays of preventing viral poultry diseases. However, the development of recombinant DNA technology in recent years has enabled the generation of recombinant virus vector vaccines, which have the advantages of preventing multiple diseases simultaneously and simplifying the vaccination schedule. More importantly, some can induce a protective immune response in the presence of maternal antibodies and offer long-term immune protection. These advantages compensate for the shortcomings of traditional vaccines. This review describes the construction and characterization of primarily poultry vaccine vectors, including fowl poxvirus (FPV), fowl adenovirus (FAdV), Newcastle disease virus (NDV), Marek’s disease virus (MDV), and herpesvirus of turkey (HVT). In addition, the pathogens targeted and the immunoprotective effect of different poultry recombinant virus vector vaccines are also presented. Finally, this review discusses the challenges in developing vector vaccines and proposes strategies for improving immune efficacy.